Spondyloarthritis and Risk of Malignancy: A Narrative Review on a Still Controversial Issue - Ennio Giulio Favalli; Francesco Grossi; Alberto Batticciotto; Matteo Filippini; Simone Parisi; Ombretta Viapiana; Paolo Gisondi; Paolo Dapavo; Lorenzo Dagna; Filippo De Braud (Rheumatology and Therapy)
Abstract Current literature regarding cancer risk in rheumatic and musculoskeletal diseases (RMDs) is particularly poor and controversial, even though the incidence of malignancy in some patients with RMDs is considered to be increased compared with the general population. Malignancy may be a major comorbidity in subjects with spondyloarthritis (SpA) as the result of multifactorial mechanisms, from disease pathogenesis to the iatrogenic effect of immunomodulating drugs. Several recommendations for screening and management of cancer risk have been developed in recent years with the aim of improving the different outcomes in these patients. The goal of this narrative review is to provide an overview of the currently available evidence on the risk of malignancy connected with RMDs and examine the association of SpA with cancer and the potential impact of its treatment with biologic and targeted synthetic disease-modifying anti-rheumatic drugs on development of malignancy.